2013
DOI: 10.1371/journal.pone.0060261
|View full text |Cite
|
Sign up to set email alerts
|

New Components of Drosophila Leg Development Identified through Genome Wide Association Studies

Abstract: The adult Drosophila melanogaster body develops from imaginal discs, groups of cells set-aside during embryogenesis and expanded in number during larval stages. Specification and development of Drosophila imaginal discs have been studied for many years as models of morphogenesis. These studies are often based on mutations with large developmental effects, mutations that are often lethal in embryos when homozygous. Such forward genetic screens can be limited by factors such as early lethality and genetic redund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Thus, the approximate location of Epi_13 was near the presumptive scutum in the lateral heminotum (near scutellum) and Epi_14 was likely in the posterior lateral heminotum (near scutum). Epi_7 approximate location was near the postnotum in the posterior heminotum since the expression of Epi_7 marker disco-r is restricted to the ventral edge of the wing (Grubbs et al, 2013) and the expression of another Epi_7 marker disco is restricted to the region giving rise to the post-alar bristles near the presumptive lateral scutum (Cohen et al, 1991).…”
Section: Cells In the Epithelial Clusters Map To Spatially Distinct Rmentioning
confidence: 99%
“…Thus, the approximate location of Epi_13 was near the presumptive scutum in the lateral heminotum (near scutellum) and Epi_14 was likely in the posterior lateral heminotum (near scutum). Epi_7 approximate location was near the postnotum in the posterior heminotum since the expression of Epi_7 marker disco-r is restricted to the ventral edge of the wing (Grubbs et al, 2013) and the expression of another Epi_7 marker disco is restricted to the region giving rise to the post-alar bristles near the presumptive lateral scutum (Cohen et al, 1991).…”
Section: Cells In the Epithelial Clusters Map To Spatially Distinct Rmentioning
confidence: 99%
“…disco-r is present within the interval implicated by X-linked QTL Q1, was shown to have lower expression in male compared with female pupal forelegs (Barmina et al , 2005) and has been suggested to be involved in leg development (Grubbs et al , 2013). pUf68 is implicated by QTL Q2 on chromosome 3.…”
Section: Discussionmentioning
confidence: 99%
“…Note, tub-Gal80 ts was not required to pass embryogenesis with Act-Gal4; however, we followed the same timing for elevating the temperature with the Act-Gal4 and Dll-Gal4 larvae. Others and we have noted a slight affect on leg development with the Dll-Gal4 driver since the Gal4 insertion compromises the Dll gene (Calleja et al, 1996;Grubbs et al, 2013). This was taken into account in all analyses.…”
Section: Methodsmentioning
confidence: 99%